Sainte-Beuve vs Eckermann, or How the First Russian Translation of “Conversations with Goethe” Was Made - Elena A. Andrushchenko (Studia Litterarum)
The article discusses a curious case of the reception of Goethe in Russia in the late 19th century — the first translation of “Conversations with Goethe” (1891), authored by D.V. Averkiev and commissioned by A.S. Suvorin. Taking the expectations of the implicit reader into account had made his newspaper and publishing house one of most successful Russian enterprises by the turn of the century. It also aligned with Averkiev’s Kulturträger attitude, both as a writer who introduced the public to the culture and everyday life of old Russia and as a translator who familiarized it with the achievements of Western European literature and science. In his translation Averkiev utilized an intermediate text, namely É. Delerot’s translation of the “Conversations” into French. He transferred not only its structural features, but also the skeptical opinion of Eckermann’s personality expressed by C.A. Sainte-Beuve in his letter to G. Charpentier. By reducing the original text, extending his translation with materials from Goethe’s correspondence and recollections about him, Delerot corrected the “wrong” genre of the source text — with the ideal seen in J. Boswell’s book on S. Johnson. Averkiev retained the essential features of the intermediate text, but complemented it with his own article as well as footnotes bringing the text closer to Russian understanding. He expanded some footnotes into detailed comments on the history of literature and theatre, which he specialized in. Having emerged in the depths of a fading culture, Averkiev’s translation anticipated the future explorations of Russian modernism, whose representatives studied the personality of Goethe via his translation and quoted the German writer’s conversations in his interpretation.